Typifications and nomenclatural notes on Neotropical Balanophoraceae - Cardoso, Leandro Jorge Telles; Braga, João Marcelo Alvarenga (Phytotaxa, 2018)
Nomenclatural types for nine names of Neotropical Balanophoraceae are designated or clarified here. The following names are lectotypified: Helosis mexicana, Langsdorffia hypogaea, L. moritziana, Lathrophytum peckoltii, Scybalium fungiforme, and S. glaziovii. For the names Helosis brasiliensis, and Thonningia mexicana, a neotype, and a second-step lectotype are respectively designated. Furthermore, the typification of the name Langsdorffia rubiginosa is clarified here.